Evaluation of electromagnetic radiation shielding characteristics of facing building materials - Панова, Олена Василівна; Краснянський, Григорій Юхимович; Азнаурян, Ірина Олександрівна (My University, 2021)
The article presents the results of theoretical studies of the protective properties of composite facing materials based on a dielectric matrix with an electrically conductive nonmagnetic filler in a wide frequency range of incident electromagnetic radiation. Expressions are got for the values of the transmission, reflection and absorption, and the electromagnetic radiation shielding efficiency calculated on their basis. The dependences of the permittivity and electrical conductivity of the composite on the volume fraction of the electrically conductive additive required for calculations were got based on the hypothesis of similarity, considering the nonzero conductivity of the dielectric matrix. Satisfactory agreement between the calculation results and the measured shielding characteristics of specimens of metal silicate materials based on calcium hydro silicates and copper powder was established. The results presented show the adequacy of the proposed calculation method and indicate that it can be used for preliminary estimates of the shielding characteristics when designing electromagnetic radiation shields based on composite facing materials.
Keywords: properties of composite materials; electrical conductivity; electromagnetic radiation; electromagnetic radiation shielding efficiency; 691:693.6]:537.531